1994
DOI: 10.1021/jm00041a015
|View full text |Cite
|
Sign up to set email alerts
|

Novel Prodrugs of Alkylating Agents Derived from 2-Fluoro- and 3-Fluorobenzoic Acids for Antibody-Directed Enzyme Prodrug Therapy

Abstract: The synthesis of six novel fluorinated potential prodrugs for antibody-directed enzyme prodrug therapy is described. The [2- and 3-fluoro-4-[bis(2-chloroethyl)amino]benzoyl]-L-glutamic acid (9 and 21), their bis(mesyloxy)ethyl derivatives (7 and 19), and their chloroethyl (mesyloxy)-ethyl derivatives (8 and 20) are bifunctional alkylating agents in which the activating effect of the ionized carboxyl function is masked through an amide bond to the glutamic acid residue. These compounds were designed to be activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
2
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 10 publications
0
13
2
1
Order By: Relevance
“…As the nitrogen mustard prodrugs we have previously synthesised did not contain fluorine, 23 we have prepared two new nitrogen mustards 8 and 18 with a fluorine tag. It must be reminded that some fluorinated nitrogen mustard prodrugs have already been reported by Springer et al, 35 but they widely differ from the prodrugs which are reported in the present study. Indeed, instead of glutamic-containing prodrugs as reported by Springer et al, 35 the prodrugs that constitute the basis of this study are phenol glucuronides.…”
Section: Introductioncontrasting
confidence: 49%
See 1 more Smart Citation
“…As the nitrogen mustard prodrugs we have previously synthesised did not contain fluorine, 23 we have prepared two new nitrogen mustards 8 and 18 with a fluorine tag. It must be reminded that some fluorinated nitrogen mustard prodrugs have already been reported by Springer et al, 35 but they widely differ from the prodrugs which are reported in the present study. Indeed, instead of glutamic-containing prodrugs as reported by Springer et al, 35 the prodrugs that constitute the basis of this study are phenol glucuronides.…”
Section: Introductioncontrasting
confidence: 49%
“…It must be reminded that some fluorinated nitrogen mustard prodrugs have already been reported by Springer et al, 35 but they widely differ from the prodrugs which are reported in the present study. Indeed, instead of glutamic-containing prodrugs as reported by Springer et al, 35 the prodrugs that constitute the basis of this study are phenol glucuronides. Compound 8 bears an analogy to Roffler's prodrug 20 in that the drug is directly linked to glucuronic acid.…”
Section: Introductioncontrasting
confidence: 49%
“…Further work indicated that two prodrugs related to CMDA: 3-fluoro-4-[bis (2-chloroethyl)amino]benzoyl-Lglutamic acid 22 and 3,5-difluoro-4-[bis(2-iodoethyl)amino]benzoyl-L-glutamic acid, 2 23 were superior to CMDA in terms of cytotoxic differential, potency, and the bystander effect in vitro and in vivo in a number of CPG2/GDEPT systems. The reasons for these improvements are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…10 since it has no mammalian homologue. 11 This enzyme catalyzes the scission of an amidic, 11,12 urethanic, or ureidic 13,14 bond between an aromatic nucleus and L-glutamic acid.…”
Section: Introductionmentioning
confidence: 99%